DCD Liver Grafts Can Safely Be Used for Recipients With Grade I–II Portal Vein Thrombosis: A Multicenter Analysis. Issue 11 (7th October 2022) - Mercado, Lydia A.; Bhangu, Harpreet K.; Calderon, Esteban; Mathur, Amit K.; Aqel, Bashar; Musto, Kaitlyn R.; Watt, Kymberly D.; Rosen, Charles B.; Bolan, Candice; LeGout, Jordan D.; Taner, C. Burcin; Harnois, Denise M.; et al.
Abstract : Background: With donation after circulatory death (DCD) liver transplantation (LT), the goal of the recipient implantation procedure is to minimize surgical complexity to avoid a tenuous environment for an already marginal graft. The presence of portal vein thrombosis (PVT) at the time of LT adds surgical complexity, yet‚ to date, no studies have investigated the utilization of DCD liver grafts for patients with PVT. Methods: All DCD LT performed at Mayo Clinic-Florida, Mayo Clinic-Arizona, and Mayo Clinic-Rochester from 2006 to 2020 were reviewed (N = 771). Patients with PVT at the time of transplant were graded using Yerdel classification. A 1:3 propensity match between patients with PVT and those without PVT was performed. Results: A total of 91 (11.8%) patients with PVT undergoing DCD LT were identified. Grade I PVT was present in 62.6% of patients, grade II PVT in 27.5%, grade III in 8.8%, and grade 4 in 1.1%. At the time of LT, thromboendovenectomy was performed in 89 cases (97.8%). There was no difference in the rates of early allograft dysfunction (43.2% versus 52.4%; P = 0.13) or primary nonfunction (1.1% versus 1.1%; P = 0.41) between the DCD PVT and DCD without PVT groups, respectively. The rate of ischemic cholangiopathy was not significantly different between the DCD PVT (11.0%) and DCD without PVT groups (10.6%; P = 0.92). Graft ( P = 0.58) and patient survival ( P = 0.08) were similar between the 2 groups. Graft survival at 1-, 3-, and 5-y was 89.9%, 84.5%, and 79.3% in the DCD PVT group. Conclusions: In appropriately selected recipients with grades I–II PVT, DCD liver grafts can be utilized safely with excellent outcomes.